A enigmática luz: - Maia, Phablo Henrique Duarte (Universidade Federal do Tocantins, 2023)
This work presents a historical panorama about the nature of light and its phenomena, which have intrigued the greatest minds of the scientific environment for a long time. Given the relevance of this issue, we present the evolution of the concept of light and its interpretation over time through the aspects of the history of science. With this work, we intent to make clear the trajectory of thoughts to construct the concepts involved in this subject, whose results culminated in the understanding we have today about light, and the formation of the pillars of Modern Physics. As a way of contributing to the understanding of the subject, since there are few historiographical and philosophical works that address the conception of light in both Western and Eastern history, and for lack of bibliography in Portuguese for the theme, we conducted a research that covered both the bibliographic and descriptive aspects of the characters who were part of the history of light.